Kajian Aqidah terhadap Praktik Law of Attraction yang Berkembang di Media Sosial Perspektif Syed Muhammad Naquib al-Attas - Ezalia Purnama Sari; Dimas Sadewa; Muhammad Iqbal Habi; Indawan; Shinta Olivia; Hafizul Husni (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The rapid development of social media has popularized self-improvement trends, notably the Law of Attraction (LoA), which posits that positive thoughts and affirmations can attract desired realities. This phenomenon raises crucial questions regarding its compatibility with Islamic creed (aqidah). This study aims to analyze the practice of LoA on social media, examine it from an Islamic aqidah perspective, and evaluate it through the intellectual framework of Syed Muhammad Naquib al-Attas. Employing a qualitative approach with a library research method, data were collected from the Qur’an, Hadith, al-Attas’s works, and relevant literature, then analyzed using descriptive-critical and content analysis methods. The findings indicate that while motivational aspects of LoA, such as optimism and goal-setting, align with the Islamic concept of ikhtiar (effort), the metaphysical claim that human thoughts or "universal energy" possess independent power to determine reality contradicts the principle of tawhid. Through al-Attas’s perspective, this phenomenon must be filtered using an Islamic worldview grounded in revelation to prevent the loss of adab. It is concluded that Muslims must be selective: adopting beneficial psychological motivation while rejecting beliefs that compromise absolute reliance on Allah.